I Want More and Better Cells! - An Outreach Project about Stem Cells and Its Impact on the General Population - Amaral, Sara Varela (2015)
Although science and technology impact every aspect of modern societies, there is still an extensive gap between science and society, which impairs the full exercise of citizenship. In the particular case of biomedical research increased investment should be accompanied by parallel efforts in terms of public information and engagement. We have carried out a project involving the production and evaluation of educational contents focused on stem cells - illustrated newspaper chronicles, radio interviews, a comic book, and animated videos - and monitored their impact on the Portuguese population. The study of the outreach materials in a heterogeneous sample of the population suggests that they are valuable tools to disseminate scientific messages, and that this is especially true for the comic-book format. Furthermore, the data showed that clear and stimulating outreach materials, that are able to teach new concepts and to promote critical thinking, increase engagement in science at different levels, depending on the depth of the concepts involved. Additionally, these materials can influence political, social and personal attitudes toward science. These results, together with the importance attributed to scientific research in stem cells by the population sampled, validates the diffusion of such materials as a significant contribution towards an overall public understanding and engagement in contemporary science, and this strategy should thus be considered in future projects. Regardless, stringent quality control must be implemented in order to efficiently communicate accurate scientific developments, and the public stimulated in terms of finding additional sources of reliable information.